A quasi experimental study of psychotherapy in reducing anxiety among nurses working in COVID 19 wards - M Zaenal; Yuliani Setyaningsih; Daru Lestantyo; May Sein Ba (Journal of Holistic Nursing Science, 2022)
Frontline nurses working with the coronavirus disease‐2019 (COVID‐19) pandemic face various mental health problems ranging from excessive stress and severe anxiety. If left untreated, this will reduce productivity and nursing care. However, a study addressing this issue among nurses in Indonesia is limited. Therefore, this study investigates psychotherapy to reduce anxiety in a group of nurses. The study used an experimental design with one group pre-posttest design. A total of 54 clinical nurses were involved after signing informed consent. Hamilton anxiety rating scale was engaged for the data collection process. Paired sample t-test was used for data analysis. The finding shows that psychotherapy helps to reduce anxiety due to the pandemic (p < 0.05). Further study is needed to evaluate the effectiveness of using groups of nurses working in Hospitals. Keywords: anxiety; psychotherapy; COVID -19; nursing practice; mental health care